2024
DOI: 10.2147/ijn.s443812
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing Psoriasis Topical Treatment: Enhanced Efficacy Through Ceramide/Phospholipid Composite Cerosomes Co-Delivery of Cyclosporine and Dithranol: In-Vitro, Ex-Vivo, and in-Vivo Studies

Sammar Elhabal,
Nashwa Abdelaal,
Saeed Al-Zuhairy
et al.

Abstract: Purpose Improving the treatment of psoriasis is a serious challenge today. Psoriasis is an immune-mediated skin condition affecting 125 million people worldwide. It is commonly treated with cyclosporine-A (CsA) and dithranol (DTH). CsA suppresses the activation of T-cells, immune cells involved in forming psoriatic lesions. Meanwhile, DTH is a potent anti-inflammatory and anti-proliferative drug that effectively reduces the severity of psoriasis symptoms such as redness, scaling, and skin thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The reduction in LPS-induced wound inflammation, either by promoting IL-10 or inhibiting IL-6, TNF-α, and IL-1β, has been highlighted by previous studies. 44 Our investigation revealed that AO-ZnO-NPs-chitosan gel treatment resulted in a significant decrease in serum levels of IL-6, TNF-α, and IL-1β, along with an increase in IL-10 levels three hours after LPS injection, when compared to Althaea Officinalis extract. Therefore, we propose that the modulation of immunoregulatory cytokines is how AO-ZnO-NPs-chitosan gel achieves enhanced therapeutic benefits in wound healing.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The reduction in LPS-induced wound inflammation, either by promoting IL-10 or inhibiting IL-6, TNF-α, and IL-1β, has been highlighted by previous studies. 44 Our investigation revealed that AO-ZnO-NPs-chitosan gel treatment resulted in a significant decrease in serum levels of IL-6, TNF-α, and IL-1β, along with an increase in IL-10 levels three hours after LPS injection, when compared to Althaea Officinalis extract. Therefore, we propose that the modulation of immunoregulatory cytokines is how AO-ZnO-NPs-chitosan gel achieves enhanced therapeutic benefits in wound healing.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, when applied to cells, the AO-ZnO-NPs-chitosan gel exhibited a significant increase in flow, particularly in response to stimuli like acute inflammation or oxidative stress. 44 This suggests that the gel formulation may provide a sustained release of proteins, thereby enhancing their bioavailability even in compromised skin conditions. Given that the components of the formulation are generally considered safe, these findings support the biocompatibility of the AO-ZnO-NPs-chitosan gel when in contact with skin cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 66 ] Ceramide, hyaluronic acid, edge activator 222.36 ± 0.36 nm Thin film hydration method Cyclosporine-A, dithranol C57BL/6 mice Cyclosporine-A and dithranol, which have limited oral bioavailability, were encapsulated in ceramide/phospholipid composite cerosomes to enhance skin penetration and exert antiproliferative effects. [ 67 ] 7 Emulsion Drug Delivery Systems Fish oil, linseed oil, tween 80, transcutol-P <130 nm Spontaneous emulsification method, high pressure homogenization technique Tacrolimus Albino mice The intervention enhances medication efficacy by minimizing irritation and promoting greater patient compliance. [ 68 ] Span 80, tween 80 16.46 ± 0.07 nm - Tacrolimus SD rats, BALB/c mice It enhances medication solubility and permeability, acting as an adjuvant in anti-psoriasis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a CsA/DTH solution, the cerosomes enhanced drug penetration by 66.7% and decreased PASI by 2.73-fold and 42.85%, respectively. 67 …”
Section: Discussionmentioning
confidence: 99%